1993
DOI: 10.1037/0096-1523.19.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Role of image acceleration in judging landing location of free-falling projectiles.

Abstract: The vertical acceleration of the projective image of a free-falling object specifies whether the object will land behind or in front of the observation site. Human sensitivity to this visual cue was investigated in 4 studies. Experiments 1 and 2 examined sensitivity to both constant and accelerating vertical acceleration. Detection of acceleration required a total change in velocity that was about 20% of the average velocity. In Experiments 3 and 4, subjects judged where computer-simulated free-falling objects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(100 citation statements)
references
References 22 publications
2
98
0
Order By: Relevance
“…Babler & Dannemiller, 1993;Calderone & Kaiser, 1989). The time courses of these two variables are very similar, but there are differences.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Babler & Dannemiller, 1993;Calderone & Kaiser, 1989). The time courses of these two variables are very similar, but there are differences.…”
Section: Resultsmentioning
confidence: 94%
“…Catchers were videotaped, and their running patterns were determined from the digitized video images. Michaels and Oudejans showed that their participants indeed ran in a way that tended to keep optical speed constant throughout the run (optical speed deviated from con-3 Although studies asking observers to judge the future passing side (in front or behind) of (simulated) balls might provide evidence that observers make these judgments on the basis of optical acceleration (e.g., Babler & Dannemiller, 1993;Michaels & Oudejans, 1992), the use of optical acceleration in such a task cannot be generalized to the adherence to a Chapman Strategy, which claims a continuous control of locomotion on the basis of that variable. Later in this article we present further evidence that one needs to study the situation with locomotion to make claims on the use of the variables implied in the control of locomotion.…”
Section: Do Catchers Adhere To the Chapman Strategy?mentioning
confidence: 99%
See 1 more Smart Citation
“…In the second experiment, we used an indirect interceptive task in which participants intercepted a moving stimulus using a ball 3 Some recent studies have tried to test Chapman's (1968) hypothesis, according to which locomotor displacements required to catch a ball in flight could depend directly on the perception of the acceleration of the ball (e.g., Babler & Dannemiller, 1993;Brouwer et al, 2002;P. McLeod, Reed, & Dienes, 2001;Michaels & Oudejans, 1992;Oudejans, Michaels, Bakker, & Davids, 1999).…”
Section: Synthesismentioning
confidence: 99%
“…When you follow this heuristic, you will be there when the ball hits the ground. As it happens, baseball players are very poor at predicting where a ball is going to hit the ground when they are asked not to run towards it (Babler & Dannemiller, 1993). They just manage to get there when the ball does.…”
Section: )mentioning
confidence: 99%